(untitled) (Context: Journal of Interdisciplinary Studies, 2022)
Åsa Wikfors, Alternativne činjenice: o znanju i njegovim neprijateljima, Zagreb: Naklada OceanMore, 2021. 120 str., ISBN 978-953-332-120-2.